Economic and environmental assessment of a green pavement recycling solution using foamed asphalt binder based on LCA and LCCA - Hongmei Li; Jiwang Jiang; Qiang Li (Transportation Engineering, 2023)
Cold-in-place recycling with foamed asphalt binders (CIR-F) has been considered as an environmentally sustainable option for asphalt pavement maintenance due to the low mixing temperature and the reuse of up to 100% of existing asphalt materials. However, the quantitative assessment of its economic and environmental performance from a life cycle perspective has rarely been addressed in the literature. To fill in the gap, this study conducted cradle-to-laid life cycle assessment (LCA) and life cycle cost analysis (LCCA) to estimate the annual energy consumption, carbon emissions, and equivalent uniform annual cost (EUAC) of CIR-F and compared it with the traditional mill & fill (M&F). The considered life cycle stages include raw material production, construction, transportation, and work zone traffic management. The heat map visualization technique was employed to explore the influence of service life on the relative environmental and economic advantages of CIR-F. The results show that both economic and environmental impacts of CIR-F were significantly reduced compared to conventional M&F, with 66.45% less cost, 59.62% less energy consumption and 45.73% less carbon emissions. Reducing the service life of CIR-F will reduce, or even completely offset, its benefits over M&F. Assuming a service life of 15 years for conventional M&F, the service life of CIR-F needs to be greater than 8 years to maintain its environmental advantage. The results of this study provide a quantitative assessment of the economic and environmental benefits of CIR-F, providing evidence for its broader application.